Restatement of religion : Swami Vivekananda and the making of Hindu nationalism - Sharma, Jyotirmaya (New Haven Yale University Press, 2013)
Offers a portrait of Swami Vivekananda and his relationship with his guru, the legendary Ramakrishna. This work focuses on Vivekananda's reinterpretation and formulation of diverse Indian spiritual and mystical traditions and practices as "Hinduism" and how it served to create, distort, and justify a national self-image.
Includes bibliographical references and index.
Keywords: Vivekananda; Ramakrishna; Hinduism and politics; Hindutva; Nationalism